Optimal consumption choice for ratchet investors - Frank Riedel (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 2001)
The utility maximization problem of ratchet investors who do not tolerate any decline in their consumption rate is solved explicitly for all felicity functions in a Markovian framework which includes Brownian motion and Poisson processes as special cases. The optimal consumption plan turns out to be the running maximum of the optimal plan a conventional time-additive investor would choose.
urn:nbn:de:kobv:11-10051094
Keywords: D91; 330; Intertemporal Consumption Choice; Habit Formation; Non-Time Separable Utility